Analisis Pendapatan Asli Daerah dan Belanja Pembangunan terhadap Pertumbuhan Ekonomi di Kabupaten/Kota Jawa Timur - Muhammad Yasin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Economic growth is a change in the economic process in a country in a sustainable direction for the better in a certain period. Economic growth can also be interpreted as a process of increasing the production capacity of an economy that is realized in the form of an increase in national income. PAD-Free Variables (X1) Measured using: (1) Taxes, (2) Non-taxation, Development Expenditures (X2) Measured using: (1 ) Development, (2) Growth. Economic Growth Variable (Y) Measured using: (1) Efficiency ratio, (2) Effectiveness Ratio, (3) Independence ratio, (4) Ratio of economic growth activity.This means that if the income of the region will also cause an increase in economic growth achievements. which is very flexible in terms of utilization causes the regions to be more flexible in planning the allocation of expenditure budgets for development activities in accordance with their economic agenda which includes the development of basic facilities and infrastructure that play a role in supporting optimal economic growth. Keywords: PAD, Development Expenditure, Economic Growth